Edge Effect Intensity in Agroforestry Ecotones Under Fire Disturbance Scale - Chen, Guohui; Gao, Zhongliang; Fu, Lianli; Dong, Kaixun; Ma, Xiaojie; Li, Na; Chen, Wenquan; Pu, Xiaohui; Zhou, Ming (International Journal of Natural Resources and Environmental Studies, 2025)
Edge effect is a key concept in ecology and biodiversity conservation, playing a vital role in studying ecological processes at the ecosystem and landscape scales. Drawing on the concept, mechanisms, and connotations of edge effects, this paper analyzes the impacts of fire disturbance on agro-forest ecotones from multiple angles. Six indicators, including the Shannon-Wiener index, Simpson index, Margalef index, Pielou evenness index, tree height, and average diameter of new shoots, are used to assess edge effect intensity. By examining how fire disturbance affects ecosystem structure, species composition, and functions, this study aims to quantify its impacts on biodiversity and ecological processes in agro-forest ecotones. The findings provide a scientific basis for ecological restoration, fire prevention strategies, and forest management, helping to mitigate fire risks and protect regional ecosystems and biodiversity.